Pengaruh Kualitas SDM terhadap Daya Saing UMKM di Magelang Raya - Ida Uliyah; Ariq Fikria Niagasi; Lia Nida Husniati; Cici Tri Utami (Jurnal Ilmiah Manajemen dan Kewirausahaan, 2026)
The rapid growth of MSMEs in Magelang has contributed significantly to increasing the income of the surrounding community. However, many MSMEs still face challenges in competing in the market and have not been able to develop optimally, despite Magelang being a popular tourist destination attracting both domestic and international visitors. As the number of MSMEs grows, it is crucial to enhance the quality of human resources to support MSME businesses in order to improve their competitiveness in the market. This study focused on MSMEs in Magelang City and Regency, using a sample of 60 MSMEs, with data processed using PLS 3.0. The results of the study revealed a positive influence of the quality of human resources on the competitiveness of MSMEs in Magelang. This highlights the importance of investing in human resource development to ensure the sustainability and competitiveness of MSMEs in a rapidly growing market environment. By improving the capabilities of human resources, MSMEs can better position themselves to succeed in both local and global markets.